2019
DOI: 10.3390/su11226358
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of an Exhaust Reduction System in Fire Stations

Abstract: Firefighters are known to be exposed to a variety of hazardous materials and combustion products during operational and training activities, as well as in fire stations. However, exposure to diesel exhaust emissions, classified as carcinogenic to humans by the International Agency for Research on Cancer (IARC), is also present in the fire station environment. In this study, concentrations of elemental carbon (EC), which is a surrogate of diesel exhaust and indoor air pollutants, has been measured to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…As a result, it was confirmed that, out of 11 evaluation items, carbon dioxide, total volatile organic compounds, sulfuric acid, and formaldehyde 4 exceeded domestic and foreign standards [21]. In addition, the smoke reduction device installed in the garage of the fire department reduced various harmful substances, including elemental carbon and fine dust [23]. This means that chemically harmful factors generated at the fire scene are entering the fire department through the medium of firefighters and fire fighting vehicles that were active at the fire scene.…”
Section: Introductionmentioning
confidence: 83%
“…As a result, it was confirmed that, out of 11 evaluation items, carbon dioxide, total volatile organic compounds, sulfuric acid, and formaldehyde 4 exceeded domestic and foreign standards [21]. In addition, the smoke reduction device installed in the garage of the fire department reduced various harmful substances, including elemental carbon and fine dust [23]. This means that chemically harmful factors generated at the fire scene are entering the fire department through the medium of firefighters and fire fighting vehicles that were active at the fire scene.…”
Section: Introductionmentioning
confidence: 83%
“…Toxic substances such as benzo[a]pyrene (PAH), carbon monoxide (CO), formaldehyde (HCHO), hydrogen cyanide (HCN), organophosphate flame retardants (OPFRs), and polybrominated diphenyl ethers (PBDEs) are generated at a fire scene. In addition, toxic substances such as 1,3-butadiene, benzene, toluene, xylene, HCHO, hydrogen chloride, HCN, ammonia, CO, and nitric acid are generated during live fire training for the purpose of educating firefighters [ 1 , 2 , 3 ]. Consequently, firefighters are constantly and repeatedly exposed to all these environments.…”
Section: Introductionmentioning
confidence: 99%
“…Firefighters are exposed to a wide range of toxic chemicals due to combustion (volatile organic compounds, semi-volatile organic compounds, and metals) (Engelsman et al, 2020). On the other hand, firefighters may be exposed to diesel exhaust, which is classified as a Group 1 carcinogen by the International Agency for Research on Cancer (IARC) and particulate matter (PM) from vehicles and off-gas (volatile organic compounds (VOCs), formaldehyde, among others) emitted from idling vehicles and firefighting equipment, such as clothes, boots, and gloves, from the fire scene (Kim et al, 2019). Due to the complexity in the administrative organization and its work processes, it is hard to evaluate the multiple risks and demands to which firefighters are exposed.…”
Section: Introductionmentioning
confidence: 99%